Seasonal Tidal Dynamics in the Qiantang Estuary: The Importance of Morphological Evolution - Xie, Dongfeng; Wang, Zheng Bing (Frontiers in Earth Science, 2021)
Despite the increasing number of studies on the river-tide interactions in estuaries, less attention has been paid to the role of seasonal morphological changes on tidal regime. This study analyzes the seasonal interplay of river and tide in the Qiantang Estuary, China, particularly focusing on the influences of the active morphological evolution induced by the seasonal variation of river discharge. The study is based on the high and low water levels at three representative stations along the estuary and daily river discharge through 2015, in intermediate flow year in which a typical river flood event occurred, as well as the bathymetric data measured in April, July and November, 2015. The results show strong seasonal variations of the water level in addition to the spring-neap variation. These variations are obviously due to the interaction between river discharge and tide but can only be fully explained by including the effect of morphological changes. Two types of the influences of the variation of the river discharge on the tidal dynamics in the estuary can be distinguished: one is immediately induced by the high flow and the other continues for a much longer period because of the bed erosion and the following bed recovery. Tidal range in the upper reach can be doubled after the flood event because of bed erosion and then decrease under normal discharge periods due to sediment accumulation. Over a relatively short term such as a month or a spring-neap tidal cycle, there exist good relationships between the tidal range, tidal amplification in the upper reach and the tidal range at the mouth, and between the hydraulic head over the upper and lower reaches. Such relationships are unclear if all data over the whole year are considered together, mainly because of the active morphological evolution.